Pengembangan Modul Berbasis POE (Predict Observe Explain) Terintegrasi Nilai Keislaman Materi Jaringan Tumbuhan - Yolanda Patrica Ayu; Agil Lepiyanto (Universitas Lampung, 2019)
One of teaching materials that can be used to help learners in learning activities is a module. Islamic values can be taught to learners in learning activities, including biology learning. The purpose of this development is to produce POE-based module (Predict Observe Explain) that integrate on Islamic values on the plant tissue material at XI grade of Senior High School (SMA). Data analysis of validation result of module design evaluation got 82,4% percentage so it can be classified as